Traffic engineering towards the assurance of quality in IP networks: trends and perspectives - Fafali, Paraskevi; Despotopoulos, Y.; Patrikakis, Charalampos Z.; Minogiannis, N. (Revista Colombiana de Computación, 2003)
The need for establishing bandwidth guaranteed paths in IP networks and the requirement for making optimal use of the available resources becomes more and more crucial due to the significant development of data-intensive multimedia applications. In this paper, we discuss the techniques and the mechanisms for exercising traffic engineering in contemporary IP networks under the prism of exploiting historical monitoring information collected from the operational environment. Keywords: Traffic engineering, history monitoring information, traffic matrix, QoS.